2021
DOI: 10.1016/j.jhepr.2021.100289
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatocellular carcinoma after HCV eradication: Determining the role of portal hypertension by measuring spleen stiffness

Abstract: LSM-SVR24 ≤10 kPa HCC surveillance MODERATE LSM-SVR24 10-20 kPa and SSM-SVR24 ≤42 kPa HIGH LSM-SVR24 >20 kPa or SSM-SVR24 >42 kPa No surveillance, US yearly US-based surveillance every 6 months (±AFP) Closer follow-up by US alternated to CT/(a)MRI Non-invasive assessment HCC risk LSM SSM Highlights Portal hypertension plays an important role in liver carcinogenesis after DAA treatment.SSM is an independent predictor of HCC development after viral eradication, with a best cut-off of 42 kPa.An algorithm based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…(81) The authors found that SS significantly correlated with changes in HVPG following NSBB therapy (r = 0.784; P<0.0001) while LS measured by TE did not (r = 0.107, P = 0.655). (81) Importantly, a ≥10% decrease in SS was an excellent predictor of HVPG response to NSBBs (area under the receiver Wang et al (104) HBV, cACLD VCTE Rule out HRV: ≤46 kPa n = 341 Dajti et al (73) ACLD Low-risk VNT: ≤46 kPa Dajti et al (120) HCV-related ACLD VCTE High-risk HCC: >42 kPa n = 140…”
Section: Liver Stiffness Versus Spleen Stiffnessmentioning
confidence: 99%
“…(81) The authors found that SS significantly correlated with changes in HVPG following NSBB therapy (r = 0.784; P<0.0001) while LS measured by TE did not (r = 0.107, P = 0.655). (81) Importantly, a ≥10% decrease in SS was an excellent predictor of HVPG response to NSBBs (area under the receiver Wang et al (104) HBV, cACLD VCTE Rule out HRV: ≤46 kPa n = 341 Dajti et al (73) ACLD Low-risk VNT: ≤46 kPa Dajti et al (120) HCV-related ACLD VCTE High-risk HCC: >42 kPa n = 140…”
Section: Liver Stiffness Versus Spleen Stiffnessmentioning
confidence: 99%
“…Clinically significant portal hypertension and related LREs may not be radically abolished, despite SVR or a decrease in LS [ 4 , 37 ]. Future LRE-predicting algorithms should employ a combination [ 38 ] of LS and spleen stiffness measurements, including delta values [ 39 , 40 ], to maximize the diagnostic performances, as well as by considering remnant portal hypertension after antiviral treatment completion. Sixth, concerns and controversies regarding differences in HCC risk after viral eradication by IFN- or DAA-based therapies have been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…These results were validated in a cohort of cACLD patients. Spleen stiffness does not decrease after viral eradication, as opposed to liver stiffness [ 29 ], and it seems to be able to predict the risk of HCC [ 30 ]. Thus, the association between spleen stiffness and HVPG after viral eradication should be investigated to assess the potential role of spleen stiffness in the surveillance of CSPH after SVR.…”
Section: Impact On Clinically Significant Portal Hypertensionmentioning
confidence: 99%